2018
DOI: 10.1007/s12029-018-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors Risk of Recurrence Stratification by Tumor Volume is a Best Predictor Compared with Risk Based on Mitosis and Tumor Size

Abstract: Tumor volumetry calculated in the surgical specimen and/or pre-operative tomography was superior to the NIH consensus in stratifying the risk of recurrence in GIST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…By contrast, gastric stromal tumors (GSTs) are the most common gastrointestinal mesenchymal tumors, 4,5 of which 20% to 50% are malignant with high risk of recurrence and metastasis, resulting in a poor prognosis. [6][7][8][9] Both GLs and small GSTs tend to have similar clinical presentations and imaging findings so they could be easily misdiagnosed, highlighting the imperative need for preoperative accurate differentiation of GLs from small GSTs.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, gastric stromal tumors (GSTs) are the most common gastrointestinal mesenchymal tumors, 4,5 of which 20% to 50% are malignant with high risk of recurrence and metastasis, resulting in a poor prognosis. [6][7][8][9] Both GLs and small GSTs tend to have similar clinical presentations and imaging findings so they could be easily misdiagnosed, highlighting the imperative need for preoperative accurate differentiation of GLs from small GSTs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite equal gender distribution in adult GIST populations, female sex predominated in pediatric GIST, as has been reported previously [ 4 , 18 ]. Gastric GIST accounts for approximately 50% of all cases encountered in the general population [ 7 , 12 , 16 ] whereas the vast majority of pediatric GIST tumors (> 80%) are located in the stomach as reported here and by Benesch et al [ 18 ]. Previously, male sex [ 2 , 19 ] and non-gastric location [ 2 ] have been identified as adverse prognostic factors in GIST.…”
Section: Discussionmentioning
confidence: 56%
“…Tumor size is an identified risk factor for poor prognosis in GIST [ 7 , 11 , 12 ]. Similarly, a higher mitotic index is a predictor of tumor recurrence and/or metastatic disease [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 56 patients with liver metastasis suggested that 3D volume was a better method to evaluate the risk of liver metastasis after imatinib treatment than the tumor long axis [14]. In addition, a recent study of patients with metastatic as well as non-metastatic GIST found that tumor volume was a better measure of the risk of recurrence than the maximum length or the mitotic count [9].…”
Section: Discussionmentioning
confidence: 99%
“…Since GISTs are not spherical, it was thought that assessing tumor volume would be more helpful than measuring tumor size (longest dimension). Therefore, recent studies have used volume for evaluating the metastatic and malignant potential of GISTs [8][9][10]. The Choi criteria have been developed for assessing responses to imatinib in GIST patients, and a method of evaluating responses by combining morphological tumor response and biological response (tumor density, CT attenuation coefficient (Hounsfield units [HU]) has been presented.…”
Section: Introductionmentioning
confidence: 99%